The Effect Of The Murder Learning Method On Students' Learning Outcomes In Pai Learning At SMK PGRI 1 Pasuruan - Fitri, Rosyidah Nikmatul; Halimah, Siti (-, 2025)
This study aims to determine the effect of the Murder learning method on students' learning outcomes in Islamic Religious Education (PAI) learning at SMK PGRI 1 Pasuruan. This research is a quantitative study with an experimental approach. The research design used is the pretest-posttest control group design. The population in this study consisted of all students of SMK PGRI 1 Pasuruan, with two randomly selected classes as samples, namely the experimental class and the control class. The experimental class was taught using the Murder learning method, while the control class was taught using the conventional lecture method. Data were collected through learning outcome tests and analyzed using a t-test. The results showed that there was a significant effect of the Murder learning method on improving students' learning outcomes in Islamic Religious Education subjects. Therefore, the Murder learning method can be used as an effective alternative learning strategy to enhance students’ understanding and active participation in PAI learning.